A SYSTEMATIC REVIEW ON THE INFLUENCE OF BOARD GOVERNANCE AND SUSTAINABILITY REPORTING - Khamsi, Che Abdul Hamid; Hairul Azlan, Annuar; Fatima, Abdul Hamid; Mohd Mahyudi, Mohd Yusop; Asri, Marsidi (UNIMAS Publisher, 2025)
Sustainability reporting has become the primary method used by large corporations to inform stakeholders about the sustainability practices of the companies. Even though research on sustainability has gain prominence globally, there is still limited literature specifically on board governance and sustainability reporting of listed corporations. Therefore, it is vital that existing literature is accumulated, organised and analysed to determine the extent and development of literature in this area of research, including an overview of the key findings. The review adheres to the publication standard, namely Reporting Standards for Systematic Evidence Synthesis (ROSES). It includes articles from two leading databases, Scopus and Web of Science, which generated a final total of 53 related studies. The review is mainly categorised into six themes: social reporting, environmental reporting, GRI-based reporting, ESG-based reporting, reporting based on the scoring system and a combination of sustainability and integrated reporting. These themes further explore board governance and other related corporate governance aspects. The findings from the thematic analysis reveal an overview of board governance on sustainability reporting according to four main themes: (1) board independence and diversity; (2) board size and meeting; (3) board committee; and (4) board remuneration. Based on the results, board size and women directors tend to encourage sustainability reporting, but board independence seems less effective. The findings of this review are crucial for enhancing stakeholder confidence and protecting shareholders' interests as this study systematically summarises findings from various countries and contexts and does not just refer to the results of a single study. This study should also be particularly useful to future researchers who plan to embark on research in the areas of governance and sustainability reporting. The gaps in this research area are identified, and recommendations for future research are proposed.